Nghiên cứu tổng hợp màu vàng Zr1-XPrxSiO4 sử dụng cho công nghiệp sản xuất gạch men - Tường, Phan Văn; Quý Sơn, Lê Đình (Vietnam Journal of Chemistry, 2014)
By using quartz sand in Thua-Thien-Hue and the necessary chemicals, we have determined the optimal conditions (firing temperature, composition) for the synthesis of the yellow pigment in the silicate zircon lattice with chromophore ion Pr4+. The synthesize pigment is the same colour characterization in comparison with the European one on the glaze of ceramic tile.